In vitro bactericidal activity of Evolvulus alsinoides L. against Helicobacter pylori - Fernando, S.S.N.; Hewageegana, H.G.S.P.; Ratnasooriya, W.D. (My University, 2006)
Recently we experimentally showed in rats, strong gastroprotective activity of Evolvulus alsinoides (Vishnukranti), which is used in the treatment of peptic ulcers in A y u r v e d a . Since Helicobacter pylori a re implicated with gastric ulcers, it is p o s s i b le that Evolvulus alsinoides may a l s o p o s s e s s e s bactericidal activity against Helicobacter pylori. T h i s was tested in vitro using d i s c diffusion method and the kill curve with four clinical strains and N C T C type I (11637) of Helicobacter pylori. T h e results showed Evolvulus alsinoides extract has promising bactericidal activity against Helicobacter pylori.